Peritoneal Dialysis and Retroperitoneal Laparoscopic Radical Nephrectomy: A Favorable Experience With a Patient Complicated by Renal Cell Carcinoma. Issue 10 (8th December 2017) - Imai, Reika; Akimoto, Tetsu; Kimura, Takaaki; Kohara, Marina; Shimizu, Toshihiro; Oka, Kentaro; Shuto, Miwa; Asakura, Maki; Nagayama, Izumi; Takeda, Shin-ichi; Yagisawa, Takashi; Muto, Shigeaki; et al.
Peritoneal dialysis (PD) is an accepted modality for managing end-stage kidney disease. We herein report a 75-year-old female patient on chronic PD who was complicated by renal cell carcinoma. She was successfully treated with retroperitoneal laparoscopic radical nephrectomy followed by a prompt resumption of the procedure. Various surgeries disturbing the abdominal wall integrity often disrupt the regular PD schedule, and using minimally invasive approaches is therefore an attractive therapeutic option. Our experience emphasizes the feasibility and safety of a retroperitoneal approach–based laparoscopic technique based on several empirical examples. However, systemic studies on this topic are obviously lacking, so we strongly recommend the accumulation of more cases similar to our own. Several surgical concerns that need to be dealt with among PD patients are also discussed.